Flow Diverter-Assisted Coil Embolization of Blood Blister-Like Aneurysm Using Semi-deploying Technique - Zhang, Ping; Zhong, Weiying; Li, Tao; Tan, Xianjun; Chen, Chao; Li, Mingxin; Li, Zhonggang; Li, Gang; Wang, Yunyan (Frontiers in Neurology, 2021)
Despite many therapeutic methods were utilized to treat blood blister-like aneurysms (BBAs), the optimal treatment approach has not yet been defined. This study presents the single center experience with BBAs treated with flow diverter-assisted coiling using semi-deploying technique, and discusses the efficacy and safety of the method. The patients with subarachnoid hemorrhages (SAH) due to BBAs and treated with Pipeline Flex Embolization Device (PED) between November 2015 and February 2019 in our hospital were retrospectively reviewed. Patient demographic data, timing of treatment, angiographic details, treatment techniques, clinical outcomes and follow-up results were recorded. Ten cases (6 women and 4 men) were enrolled. The mean age of patients was 50.7 years (range 40–61 years). The aneurysm size ranged from 2 × 1.7 mm to 4.5 × 3.8 mm. Seven patients were treated with PED assisted coil embolization using semi-deploying technique, and all of the aneurysms were totally obliterated at the follow up. One patient treated with PED assisted coil embolization suffered from parenchymal hemorrhage 3 days after the treatment, and another one patient also treated with PED and coil died of severe vasospasm 10 days after the treatment. There was no reruptured cases during the follow-up. Here we showed that PED assisted coil embolization using semi-deploying technique could be a technically safe and effective treatment for BBAs.